Educação e direito: a conexão necessária para a formação integral e integradora da criança e do adolescente junto ao ambiente escolar - Gimenez, Melissa Zani (2021)
An empirical research carried out in the early years of the first cycle of elementary school is presented, more precisely in the 3rd and 4th years, during the academic years of 2016 and 2017, held at the “EMEF Professor Antonio Andrade Guimarães”, in the city of Vera Cruz / SP. In this context, the general objective of the present research was to promote educational activities related to the Statute of the Child and Adolescent-ECA, emphasizing the precepts present in the law of nº 11.525 / 2007, to include content that deals with the rights of children and adolescents in the elementary school curriculum, in dialogue with other subjects, assessment of knowledge, behavior and attitudes before and after training. The study of the statutory diploma emerged in the classroom, as a code of ethics for children and adolescents, to contribute to citizenship education of elementary school students as human beings in the process of development, prioritizing a Doctrine of Integral Protection, providing a possibility for conflict resolution in society. Teaching-learning was built with students through collective dispute resolutions, as well as thinking about their rights and duties, as collective beings and belonging to a social system. Over the course of this educational practice, the results showed changes in behavior and conceptions, increased safety, self-esteem and argumentative ability on the part of children, higher school attendance, as well as higher attendance by parents or guardians at school meetings. This pedagogical practice highlights a trend that accompanies the development of the protection of human rights, where children are entitled to rights and not object of protection, guiding criteria for the preparation and application of child and adolescent norms. In the meantime, fraternity emerges as a lever for implementing the statutory legal order in classrooms, realizing a right belonging to minorities that are at the mercy of the majority, of adults, for a real realization of their rights. We opted for the qualitative methodological approach, which comprises the observation, recording and analysis of data through descriptive categories. Questionnaires with open questions were also used. The procedure adopted is the hypothetical-deductive method in which statutory education in classrooms is analyzed as a mechanism for building the ethical and social personality of the young citizen, developing a lifelong project, influencing not only their future, but the future of society itself